Intraabdominal Compartment Syndrome Complicating Transurethral Resection of Bladder Tumor - Sachin Narain; Jadelis Giquel; Armando Ariza; Ricardo Martinez-Ruiz; Bruce R. Kava; Christina Matadial (Case Reports in Urology)
Abdominal compartment syndrome can result from many different causes. We present a case where this dangerous syndrome occurred in the operating room during a transurethral resection of a bladder tumor. It was initially recognized by an elevation in the peak inspiratory pressure. We report the typical physiologic changes that occur with this syndrome and its treatment options.